Restes d'hadrosaure dans le Crétacé terminal marin de Larcan (Petites Pyrénées, Haute-Garonne, France) [Hadrosaur remains in the Late Cretaceous marine sediments of Larcan (Petites Pyrenees, Haute-Garonne, France)] - Bilotte Michel; Laurent Yves; Téodori Dominique (Carnets de Géologie, 2010)
The discovery of two hadrosaur fragments (maxilla and quadrate) in marine sediments of the end of the Cretaceous (uppermost Maastrichtian) is reported. Although this type of taphocoenosis is not exceptional for continental organisms, its situation at approximately 1 m under the iridium zone of the K/T boundary deserves to be emphasized.